If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 17y + -4y + 27 = 4y + -18 Reorder the terms: 27 + 17y + -4y = 4y + -18 Combine like terms: 17y + -4y = 13y 27 + 13y = 4y + -18 Reorder the terms: 27 + 13y = -18 + 4y Solving 27 + 13y = -18 + 4y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4y' to each side of the equation. 27 + 13y + -4y = -18 + 4y + -4y Combine like terms: 13y + -4y = 9y 27 + 9y = -18 + 4y + -4y Combine like terms: 4y + -4y = 0 27 + 9y = -18 + 0 27 + 9y = -18 Add '-27' to each side of the equation. 27 + -27 + 9y = -18 + -27 Combine like terms: 27 + -27 = 0 0 + 9y = -18 + -27 9y = -18 + -27 Combine like terms: -18 + -27 = -45 9y = -45 Divide each side by '9'. y = -5 Simplifying y = -5
| -4u^2+16u-9=0 | | 5x+y=17-3x | | 3y^2+7=3 | | 122-5x=2x | | 3y^2+7y=7 | | 36-(-17)-(144/16)-2 | | 5x-25=25-4x+5-2x | | 2+0.1(4-x)=1.6x-(0.2x-2.4) | | 2x/-5x^2 | | 0.14-0.05x=0.1x-0.1 | | 0.14-0.005x=0.1x-0.1 | | 0.4x+0.3=0.8x-1.3 | | X^2-x-6/-4x^2-28x-24 | | 1+y=10-4(y+1) | | 6(y-3)=-4(8+y) | | 4y+43+2y=7 | | -91=6x-15x-19 | | 5X+(X+7)=-25-2X | | 1-(1-x)*(1-x)=x+.2 | | 29=8y-7+5y | | x^2-3x+.8=0 | | 4X+(X+6)=-15-2X | | f(x)=x^2+10x+3 | | t/3-t-5/2=6 | | f(x)=x^2+10x-1 | | x/3-2(x-7)/5=4/3x | | (t/2)-(t-5)/2=6 | | x/3-2x-14/5=4/3x | | (2-6i)/(4+7i) | | -4v^2+19v-31=0 | | 4-23a=18 | | 4x^6-14x^4/2x^3 |